Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Nasabah Di BPR Mulyo Raharjo - Annisaun Nafi'ah (Universitas Merdeka Madiun, 2021)
Abstractâ€”This study aims to analyze 1) what marketing strategies have been implemented in increasing the number of customers, 2) constraints in implementing marketing strategies to increase the number of customers, 3) effective strategies in increasing the number of customers at BPR Mulyo Raharjo. This type of research uses a qualitative descriptive study. As for primary data sources, data collection techniques use interviews and documentation. This research used source triangulation and technique triangulation. Data analysis techniques are data reduction (data reduction), data display (data display) and data verification (conclusing drawing). The results of the study are 1) the strategy applied is the marketing mix using the 4P (Product, Price, Place, Promotion). 2) There are several obstacles faced including a lack of public knowledge, and a high sense of anxiety. The next obstacle lies in the credit product. 3) The most effective strategy used is the promotion approach because the role of promotion in the company is very influential and the products are in accordance with the needs of the community.Keywordsâ€”: analisis SWOT; nasabah; srategi pemasaran.Â